Study of periodic cosmic evolution in modified f (Q, T) gravity theory - Lalke, A. R.; Singh, G. P.; Bishi, B. K.
Finding a completely promising theory of gravitation that urges us to go beyond the general theory of relativity. One such approach is an extended class of symmetric teleparallel theory of gravity, namely f (Q, T ) gravity. In this work, we have explored the cosmological background of the flat FLRW universe within the framework of this theory. The cosmic transit phenomenon of the deceleration parameter is studied by employing periodic varying deceleration parameter and obtaining the exact solution of the highly non-linear field equations. The periodic scenario of cosmological models with two different Lagrangian forms of f (Q, T ) is analyzed, where the first form is linear and the second one is non-linear dependent on Q. The dynamical features of both the models, including the periodic behavior of the equation of state parameter are discussed. The self-stability and self-consistency of the derived models are tested by studying energy conditions. Additionally, the geometrical diagnostic validation of the model is also checked.
Keywords: Astrophysics